Analisis Korelasi Tingkat Inflasi Nasional Terhadap Daya Beli Masyarakat dan Angka Kemiskinan di Indonesia - Apriandi, Virgiawan Bayu; Remus Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the correlative relationship between the national inflation rate and two crucial socioeconomic variables: public purchasing power and the poverty rate in Indonesia. High inflation is suspected to have a dual impact: directly eroding the real value of income (purchasing power) and indirectly potentially increasing the number of poor people. The research method used is quantitative with a time-series data analysis approach. Secondary data was obtained from Statistics Indonesia (BPS) and Bank Indonesia over a significant period (e.g., the last 10-20 years). Data analysis was conducted using Pearson/Spearman correlation and multiple linear regression techniques to measure the strength and direction of the relationships between variables, as well as to test the significance of inflation's influence on purchasing power and poverty, while controlling for variables such as GDP growth and the unemployment rate. The results of the study are expected to empirically prove a significant negative correlation between inflation and public purchasing power, as well as a positive correlation between inflation and the poverty rate. These findings are hoped to serve as consideration for policymakers (the government and central bank) in formulating and evaluating monetary, fiscal, and social protection programs. Policy recommendations will focus on the importance of maintaining price stability as a fundamental effort to safeguard public purchasing power and prevent increased economic vulnerability leading to poverty.